Beyond Good Governances: Lesson from Forest and Cultural Governance in Pelalawan, Pangkalan Kerinci, Riau - Novi Paramita Dewi; Tauchid Komara Yuda (Policy & Governance Review, 2017)
The shift in government concept into governance takes the consequence of changes in public governance including in the forestry sector. Good forest governance becomes a great hope for managing the forest condition so that sustainable forest management can be realized. However, in its implementation, it contains a big challenge for the forest in Indonesia which is mostly identical with indigenous people. Meanwhile, the development becomes a necessity that cannot be inhibited in which business corporation as the actor who plays in the forest governance is considered as a major threat to the environment and indigenous people. To achieve good forest governance, it is necessary to have a synergy with cultural governance that is hoped to be able to accommodate the indigenous people interests. This paper is a case study related to the practice as an eﬀort to achieve good forest governance in the indigenous people of Pelalawan that are followed by the cultural governance eﬀort so that the indigenous people culture of Pelalawan that is closely related to the forest can still be maintained.